Two novel species of Lactarius subgenus Plinthogalus from Uttarakhand Himalaya - Uniyal, Priyanka; Das, Kanad; Bhatt, R.p. (Phytotaxa, 2018)
Lactarius is a prevalent ectomycorrhizal genus in the forests of Uttarakhand Himalaya. During a macrofungal exploration in the high altitude forests of this region two interesting taxa belonging to Lactarius subg. Plinthogalus were collected. Based on detailed macro- and micromorphological observations along with nrITS-based phylogenetic analysis these taxa are proposed here as new species, Lactarius nodulisporus and Lactarius singeri.